Development of intramammary delivery systems containing lasalocid for the treatment of bovine mastitis: impact of solubility improvement on safety, efficacy, and milk distribution in dairy cattle - Wang W; Song Y; Petrovski K; Eats P; Trott DJ; Wong HS; Page SW; Perry J; Garg S (Dove Medical Press, 2015)
Wen Wang,1 Yunmei Song,1 Kiro Petrovski,2 Patricia Eats,2 Darren J Trott,2 Hui San Wong,2 Stephen W Page,3 Jeanette Perry,2 Sanjay Garg11School of Pharmacy and Medical Science, University of South Australia, Adelaide, SA, Australia; 2School of Animal and Veterinary Sciences, University of Adelaide, Adelaide, SA, Australia; 3Luoda Pharma Pty Ltd, Caringbah, NSW, AustraliaBackground: Mastitis is a major disease of dairy cattle. Given the recent emergence of methicillin-resistant Staphylococcus aureus as a cause of bovine mastitis, new intramammary (IMA) treatments are urgently required. Lasalocid, a member of the polyether ionophore class of antimicrobial agents, has not been previously administered to cows by the IMA route and has favorable characteristics for development as a mastitis treatment. This study aimed to develop an IMA drug delivery system (IMDS) of lasalocid for the treatment of bovine mastitis.Methods: Minimum inhibitory concentrations (MICs) were determined applying the procedures recommended by the Clinical and Laboratory Standards Institute. Solid dispersions (SDs) of lasalocid were prepared and characterized using differential scanning calorimetry and Fourier transform infrared spectroscopy. IMDSs containing lasalocid of micronized, nano-sized, or as SD form were tested for their IMA safety in cows. Therapeutic efficacy of lasalocid IMDSs was tested in a bovine model involving experimental IMA challenge with the mastitis pathogen Streptococcus uberis.Results: Lasalocid demonstrated antimicrobial activity against the major Gram-positive mastitis pathogens including S. aureus (MIC range 0.5–8 µg/mL). The solubility test confirmed limited, ion-strength-dependent water solubility of lasalocid. A kinetic solubility study showed that SDs effectively enhanced water solubility of lasalocid (21–35-fold). Polyvinylpyrrolidone (PVP)-lasalocid SD caused minimum mammary irritation in treated cows and exhibited faster distribution in milk than either nano or microsized lasalocid. IMDSs with PVP-lasalocid SD provided effective treatment with a higher mastitis clinical and microbiological cure rate (66.7%) compared to cloxacillin (62.5%).Conclusion: Lasalocid SD IMDS provided high cure rates and effectiveness in treating bovine mastitis with acceptable safety in treated cows.Keywords: ionophore, methicillin-resistant Staphylococcus aureus, solid dispersion, intramammary drug delivery system, superbugs